Analysing Local Energy Conflicts: Outline of an Analysis Tool - Becker, Sören; Bues, Andrea; Naumann, Matthias (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
The success of the German energy transition is highly depending on developments at the local level. However, these local transitions towards a sustainable energy supply do not always run smoothly. Instead, their implementation is often troubled by local conflicts over renewable energy and new grid infrastructures. The question of public acceptance is linked to more fundamental questions such as the underlying objectives of their deployment as well as who benefits from these new facilities. These issues refer to more complex debates and negotiations on the public interest and new forms of organisations for power supply. This paper presents a tool for the analysis of local energy conflicts with special consideration of a notion of public interest and new forms of organisation. The tool links different strands of debate in the social sciences—regarding conflicts, modes of organisation and public interests—and relates them to material, spatial, temporal and actor-based issues of the energy transition. The analysis tool therefore allows an integrative reflection of energy conflicts, which has never been used in his combination so far.
Keywords: Energy transition; Conflict analysis; Public interest; New forms of organisation